Work–family conflict and anxiety among nurses of the maternal and child health institutions: the mediating role of job satisfaction - Zhao, Lipei; Wu, Jian; Ye, Beizhu; Tarimo, Clifford Silver; Li, Quanman; Ma, Mingze; Feng, Yifei; Guo, Xinghong; Song, Yalin; Zhang, Minghan; Fan, Yuanyuan (Frontiers in Public Health, 2023)
Abstract Introduction: Over the past decades, anxiety has garnered significant attention from nursing population. Investigations have centered on the correlation between work-family conflict (WFC) and anxiety as well as the link between job satisfaction and anxiety among nurses. However, the role of job satisfaction plays in the relationship between work-family conflict and anxiety remains relatively unexplored. Methods: In April 2021, a cross-sectional survey was conducted among nurses (N=3770) working at the maternal and child health institutions in Henan province, China. Multiple linear regression model was used to explore the factors associated with anxiety. Model 4 in Hayes's PROCESS macro and Bootstrap method was performed to examine the mediating role of job satisfaction in the relationship between work-family conflict and anxiety. Results: The median (interquartile range) anxiety score was 5.00 (6.00). Work-family conflict was shown to be significantly correlated to job satisfaction (r=-0.517, p<0.001) and anxiety (r=0.457, p<0.01). There was a strong negative correlation between job satisfaction and anxiety (r=-0.379, p<0.01). The study also found that nurses aged 31-40 years, those with a junior college education (p=0.001), those with an undergraduate or above education (p<0.001), those who reported experiencing work-family conflict (p<0.001), and those with lower job satisfaction (p<0.001) were more likely to experience anxiety. Additionally, job satisfaction partially (a*b=20.90%) mediated the relationship between work-family conflict and anxiety. Conclusions: The association between work-family conflict and anxiety among nurses in maternity and child health institutions was moderated by job satisfaction. Therefore, it is critical to enhance working conditions, minimize work-family conflict, and promoting job satisfaction among nurses may help to mitigate the negative effects of work-family conflict on anxiety.